We have experimented with different approaches to systems transformation — here are five insights - and Haldrup, Søren Vester (2021)
At UNDP Innovation we are on a journey to shift our approach to innovation to help tackle complex development challenges. In short, we are moving away from single point solutions, and instead we are…